VD_FINDINFO Pron / 2014 / 27 vom 13. März 2014 - VD Tribunal cantonal (2014)
TRANSACTION JUDICIAIRE, REMBOURSEMENT DE FRAISSENS GÉNÉRAL, PROTECTION DE L'UNION CONJUGALE | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 4 TFJC (2010), 67 al. 2 TFJC (2010)